FEATURES OF DIAGNOSIS OF EXTERNAL DIROFILARIASIS - I. D. Duzhiy; H. I. Piatykop; I. Ya. Gresko; O. V. Kravets; O. O. Pererva; O. L. Sytnik (Eastern Ukrainian Medical Journal, 2020)
Global environmental problems are gradually changing climatic conditions in different regions and cause significant warming. As a result, high-water beds, lakes and ponds get swamped and are colonized by blood-sucking mosquitoes, which are carriers of a number of diseases, including dirofilariasis. Manifestations of external dirofilariasis may look like ophthalmic, surgical, urological, oncological, dermatological, vascular, psychiatric diseases. The objective manifestation of the disease is the appearance of skin-subcutaneous formation, which periodically changes location. The purpose of the work: to expand the knowledge about this helminthic infection for the medical community and demonstrate the possibility of timely diagnosis. Results of the study and discussion. The authors observed 4 patients with external dirofilariasis and described 2 clinical cases. Only after surgical removal, the diagnosis was confirmed. Conclusions. Climate warming facilitates migration of blood-sucking insects from the southern regions to the north. Economic problems contribute to the increase of stray dogs and cats which are the ultimate hosts of dirofilaria. A person becomes infected through mosquito bites, which has to be considered during anamnesis data collection. The appearance of cutaneous or intradermal formations which tend to move may give grounds to diagnose lipomas, atheromas, phlebitis, lymphodenitis, "allergic reactions" after insect bites. The appearance of other symptoms such as weakness, muscle pain, joint pain, headache, eyeball pain, double vision, and sometimes nausea should suggest the possibility dirofilariasis, and focusing on the indications for surgical intervention.